INTRAVENOUS METHYLPREDNISOLONE EFFECTS ON RECTUS MUSCLES IN THYROID EYE DISEASE - Murtadha, Milzan; Supartoto, Agus; Utomo, Purjanto Tepo; Dibyasakti, Banu Aji; Darajati, Irene Titin (Majalah Oftalmologi Indonesia, 2023)
Introduction & Objective: Intravenous methylprednisolone has been used in management of Thyroid Eye Diseases (TED) which was an autoimmune inflammatory disease of the orbital tissues and the eyes. Previous study has shown benefits of intravenous methylprednisolone therapy on TED but there was need of quantitative measure to assess the effect of intravenous methylprednisolone therapy on extraocular rectus muscles. This study aimed to report the effect of high-dose intravenous methylprednisolone pulse therapy on inferior, medial, superior, and lateral rectus muscles and providing data distribution of active TED before and after therapy. Methods: Retrospective analyses were used in the data collection of patients with active Thyroid Eye Disease (TED) underwent high-dose intravenous methylprednisolone pulse therapy regiment 500mg every week for six consecutive weeks at Sardjito Eye Centre between January 2022 and December 2022. Ophthalmological investigation and quantitative computed tomography (CT) scan of the orbit were performed before and after methylprednisolone pulse therapy and demographics data were presented in tables and graphs. Results: This study included 62 eyes of 31 patients (61,3% female) with mean age of 37.8±13.47 years old. The mean thickness of Superior Rectus (SR) muscle before therapy were 4.12±2.20 mm and significantly decreased to 3.70±1.54 mm post therapy. There was no significant difference in delta mean Inferior Rectus (?IR) -0.18±1.69 (p=0.381), Medial Rectus (?MR) -0.34±1.68 (p=0.116), and Lateral Rectus (?LR) -0.33±1.94 (p=0.188) Conclusion: The treatment of Thyroid Eye Disease (TED) with high dose intravenous corticosteroid is safe and effective in reducing extraocular muscle tissue thickness with minimal side effects. Keywords: Thyroid Eye Disease, Extraocular Muscle, Intravenous Methylprednisolone Therapy.